2008
DOI: 10.1111/j.1365-2311.2007.00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Offspring performance in dynamic habitats: key factors for a riparian carabid beetle

Abstract: 1. Knowledge of the ecology of carabid species is largely restricted to adults, although larval mortality is assumed to be the key factor in overall mortality. As low-mobility larvae are unable to avoid unfavourable conditions, habitat selection of reproducing adults should be clearly affected by the habitat factors which determine offspring performance.2. The present study examines the key habitat factors governing the distribution patterns of Bembidion velox larvae and adults on the river banks of the River … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Preferential oviposition is not a likely explanation, because previous research has shown that pupae do not increase the abundance of adult carabids in field plots (Frank, 2007). Further, the short duration (15 days) of our experiments did not provide enough time for eggs to be laid, hatch, and reach second and third instars (Ernsting & Isaaks, 1997;Lundgren et al, 2005;Kleinwächter & Bürkel, 2008). As an example, at 28 • C, P. chalcites requires 4 days to hatch and an additional 34 days to reach pupation (Lundgren et al, 2005).…”
Section: Discussionmentioning
confidence: 83%
“…Preferential oviposition is not a likely explanation, because previous research has shown that pupae do not increase the abundance of adult carabids in field plots (Frank, 2007). Further, the short duration (15 days) of our experiments did not provide enough time for eggs to be laid, hatch, and reach second and third instars (Ernsting & Isaaks, 1997;Lundgren et al, 2005;Kleinwächter & Bürkel, 2008). As an example, at 28 • C, P. chalcites requires 4 days to hatch and an additional 34 days to reach pupation (Lundgren et al, 2005).…”
Section: Discussionmentioning
confidence: 83%
“…It might be assumed that eggs laid in mud would suffocate. However, ovipositioning into mud has been reported in other riparian carabids ( Carabus clatratus : [ 23 ]; Bembidion velox : [ 24 ]; Nebria yatsugatakensis : [ 25 ]). Notably, in B .…”
Section: Discussionmentioning
confidence: 99%
“…We modelled the ecological niche of the species, separately for each life stage (adult and larva), and also, the partial niches of sexes (male and female) and larval instars (larva_1, larva_2 and larva_3) (see [26], [28]). We analysed the following response variables: 1) presence-absence data (PA), where adult presence was recorded by the traps and larval presence on the maps, and 2) abundance data (AB), as the sum of distinctively identified individuals (i.e., individually marked adults and monitored larvae) recorded by the traps and on the maps.…”
Section: Methodsmentioning
confidence: 99%
“…For many species, inclusion of accurate biotic information in such broad-scale models is unfeasible [6], since the biotic niche component is too fine-grained and dynamic (e.g., [12]) to be mapped at high resolution over the entire distribution range of a species. Such a shortcoming may be critical for organisms with complex life histories (e.g., holometabolous insects; see [25]), for which detailed biological information is essential to avoid misleading interpretations of ENM results [3], [26], [27]; this is particularly important when considering conservation actions [4].…”
Section: Introductionmentioning
confidence: 99%